PENGEMBANGAN MODUL ELEKTRONIK FISIKA BERBASIS PENDEKATAN SAINTIFIK MATERI GETARAN HARMONIS MENGGUNAKAN KVISOFT MAKER - Puspitasari, Dewi Ayu; Hidayat, M; Kurniawan, Wawan (EduFisika: Jurnal Pendidikan Fisika, 2019)
This study aims to determine the final product of the physics electronics module and to determine students' perceptions of the products. The development model used is the ADDIE. The subjects of the trial were students of class XI MIA MAN 2 Tanjung Jabung Timur. The research instruments used were observation, student needs questionnaire, media ang material expert validation questionnaire, and student perception questionnaire. Data analysis techniques in the form of suggestions from the validator of media experts and material experts, while the validation questionnaire scores of media experts, material experts, and students' perceptions were carried out in descriptive statistics. The product produced is a physics electronic module with made using the KVisoft Flipbook Maker application which contains colors, images, animations, simulations, videos and examples of interactive questions. The product was declared eligible by the validator after going through the stages of validation of material experts and media experts totaling 30 and 63 with the agreed category. The results of the analysis of student perceptions in the trial obtained score 78.17 categorized as very agree.